2021
DOI: 10.1371/journal.pone.0252434
|View full text |Cite
|
Sign up to set email alerts
|

Access experiences and attitudes toward abortion among youth experiencing homelessness in the United States: A systematic review

Abstract: Objectives We sought to review the literature on the access experiences and attitudes toward abortion among youth experiencing homelessness in the United States. Methods We conducted a systematic review of peer‐reviewed literature published from 2001 to 2019. We included qualitative studies involving US participants that focused on access experiences, views, or accounts of unintended pregnancy and/or abortion among youth experiencing homelessness. We excluded studies published before 2001 as that was the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Many studies discussed barriers or challenges PEH face when it comes to surgical care, including 48 primary studies, 19 , 31 , 34 36 , 39 41 , 43 45 , 47 50 , 54 , 55 , 57 64 , 66 , 69 , 72 , 73 , 75 , 79 81 , 86 , 91 , 96 , 98 , 100 , 102 105 , 107 109 , 111 , 112 , 114 , 116 9 abstracts, 37 , 38 , 42 , 52 , 77 , 84 , 101 , 106 , 118 5 literature reviews, 22 , 74 , 95 , 99 , 110 1 invited article, 51 1 magazine article, 70 1 thought piece, 92 1 ethical essay, 115 1 thesis, 71 and 1 historical analysis. 117 The majority of comments presented concerns regarding living conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies discussed barriers or challenges PEH face when it comes to surgical care, including 48 primary studies, 19 , 31 , 34 36 , 39 41 , 43 45 , 47 50 , 54 , 55 , 57 64 , 66 , 69 , 72 , 73 , 75 , 79 81 , 86 , 91 , 96 , 98 , 100 , 102 105 , 107 109 , 111 , 112 , 114 , 116 9 abstracts, 37 , 38 , 42 , 52 , 77 , 84 , 101 , 106 , 118 5 literature reviews, 22 , 74 , 95 , 99 , 110 1 invited article, 51 1 magazine article, 70 1 thought piece, 92 1 ethical essay, 115 1 thesis, 71 and 1 historical analysis. 117 The majority of comments presented concerns regarding living conditions.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , 69 Studies commented on how PEH can have difficulty accessing medical care, resulting in fragmented or atypical health care utilization. 22 , 43 , 49 , 51 , 59 , 73 , 74 , 84 , 100 , 108 110 Specifically, 11 studies commented on challenges for PEH accessing specialty care. 36 , 41 , 43 , 60 , 75 , 92 , 99 , 100 , 103 , 111 , 112 Four studies mentioned their overreliance on visits to the emergency department.…”
Section: Resultsmentioning
confidence: 99%
“…These findings highlight the importance of increasing knowledge about the benefits of pregnancy planning and the need for access to effective reproductive services, including pregnancy prevention. Previous research revealed several barriers to pregnancy prevention services among homeless women, including fear of judgement from their family and partners about abortion or contraceptive use (Begun et al., 2020; Munro et al., 2021). There is a need to create awareness and clarify misconceptions about pregnancy prevention services among families and partners to build a nonjudgmental and supportive network for women.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study (Begun et al., 2020), young discussed keeping unwanted pregnancies for fear of negative reactions from family and disapproval from male partners toward abortion. Youth perceived that they could not make autonomous decisions about abortion as they were influenced by economic hardships, poor social support, and limited knowledge about accessing abortion services (Begun et al., 2020; Munro et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews examining the reproductive experiences of unhoused women have focused on American youth's attitudes and experiences accessing abortion (Munro et al, 2021) and factors impacting the use of prenatal care among unhoused women in the United States and Europe (McGeough et al, 2020). Guided by the reproductive justice framework, this review is the first to examine barriers to reproductive choice through the inclusion of barriers to contraception, abortion, and prenatal care.…”
Section: Discussionmentioning
confidence: 99%